Politeness Strategy and Mitigation in Food Evaluations of Nick DiGiovanni’s YouTube Reviews - Fanny Meilani NH; Dewi Kustanti; Toneng Listiani (Journal of English Language and Education, 2026)
Digital communication has reshaped how evaluations are expressed in public platforms, particularly on YouTube, where food reviews combine entertainment and judgment. However, limited attention has been given to how reviewers balance criticism and politeness in such contexts. This study aims to examine politeness strategies and mitigation devices used in food review videos by Nick DiGiovanni. Using a qualitative descriptive approach, the study applies Brown Levinson’s politeness theory and Fraser’s mitigation framework to analyze evaluative utterances from selected videos published between 2024 and 2025. The findings reveal that negative politeness strategies are dominant and frequently combined with mitigation devices such as hedges, disclaimers, and parenthetical verbs. These features function to soften criticism, maintain audience engagement, and preserve the speaker’s credibility. Overall, the study shows that politeness and mitigation play a crucial role in shaping evaluative discourse in digital media.